A Techno-economic evaluation of repurposing retired electric vehicle batteries in off-grid EV charging stations in Kenya - Mukoya, L. B. (Strathmore University, 2025)
Urban air pollution is becoming a major environmental and public health issue in Kenyan cities; thus, Kenya has taken great steps in policy development to reduce automobile emissions. A major step towards the achievement of this goal is through adoption of electric mobility. Battery powered EVs are becoming a predominant technology worldwide, including in Kenya. These vehicles and the global transition to electric mobility have spurred studies on EV battery manufacture, battery technology, and end of life management. This research has reviewed end-of-life EV batteries through a second use application in energy storage and charging support in off-grid EV charging stations. This was achieved through estimating the volumes of batteries that will be available for second life application by 2030. Further, the economic implications of reusing EV batteries in ESS and charging support for off grid charging stations were studied. The research concluded that there would be a sufficient volume of second life batteries in Kenya in the next 15 years for use in secondary applications, including off-grid EV charging stations. The electric motorcycles were particularly visible as their adoption trends showed potential to grow rapidly unlike the motor vehicles hence the need to commit further research to identifying potential reuse and repurposing pathways, especially due to their lower battery capacities. The number of registered EVs in Kenya is anticipated to reach 55,199 in 15 years, an estimate from the CAGR projections of 3.39% for motorcycles and (4.68%) for passenger vehicles. Further the volume of expired EV batteries available for reuse is estimated to reach 102,512kWh. The study further investigates the economic prospects of an off-grid EV charging station with an ESS utilizing second life batteries and concludes that the venture is expected to have a BESS lifespan of 4 years. In addition, the price of a SLB pack was computed to give the best NPV at 16.65USD per kWh further highlighting the need to lower the price of second life batteries through government incentive schemes that promote their use in secondary applications. In addition, the state of health of the battery is determined as a significant factor in the computation of the second life battery cost. Keywords: End of life battery, Energy Storage Systems, Electric Vehicle, Second-Life Battery, State of Health
Full - text thesis